Intraobserver Repeatability and Interobserver Reproducibility of Ellipsoid Zone Measurements in Retinitis Pigmentosa - Strampe, Margaret R. (Transl Vis Sci Technol, 2018)
PURPOSE: To examine repeatability and reproducibility of ellipsoid zone (EZ) width measurements in patients with retinitis pigmentosa (RP) using a longitudinal reflectivity profile (LRP) analysis. METHODS: We examined Bioptigen optical coherence tomography (OCT) scans from 48 subjects with RP or Usher syndrome. Nominal scan lengths were 6, 7, or 10 mm, and the lateral scale of each scan was calculated using axial length measurements. LRPs were generated from OCT line scans, and the peak corresponding to EZ was manually identified using ImageJ. The locations at which the EZ peak disappeared were used to calculate EZ width. Each scan was analyzed twice by each of two observers, who were masked to their previous measurements and those of the other observer. RESULTS: On average, horizontal width (HW) was significantly greater than vertical width (VW), and there was high interocular symmetry for both HW and VW. We observed excellent intraobserver repeatability with intraclass correlation coefficients (ICCs) ranging from 0.996 to 0.998 for HW and VW measurements. Interobserver reproducibility was also excellent for both HW (ICC = 0.989; 95% confidence interval [CI] = 0.983–0.995) and VW (ICC = 0.991; 95% CI = 0.985–0.996), with no significant bias observed between observers. CONCLUSIONS: EZ width can be measured using LRPs with excellent repeatability and reproducibility. Our observation of greater HW than VW is consistent with previous observations in RP, though the reason for this anisotropy remains unclear. TRANSLATIONAL RELEVANCE: We describe repeatability and reproducibility of a method for measuring EZ width in patients with RP or Usher syndrome. This approach could facilitate measurement of retinal band thickness and/or intensity.